Nutraceutical Effects of Lycopene in Experimental Varicocele: An “In Vivo” Model to Study Male Infertility - Pietro Antonuccio (Nutrients, 2020)
Varicocele is one of the main causes of infertility in men. Oxidative stress and consequently apoptosis activation contribute to varicocele pathogenesis, worsening its prognosis. Natural products, such as lycopene, showed antioxidant and anti-inflammatory effects in several experimental models, also in testes. In this study we investigated lycopene effects in an experimental model of varicocele. Male rats (n = 14) underwent sham operations and were administered with vehicle (n = 7) or with lycopene (n = 7; 1 mg/kg i.p., daily). Another group of animals (n = 14) underwent surgical varicocele. After 28 days, the sham and 7 varicocele animals were euthanized, and both operated and contralateral testes were weighted and processed. The remaining rats were treated with lycopene (1 mg/kg i.p., daily) for 30 days. Varicocele rats showed reduced testosterone levels, testes weight, Bcl-2 mRNA expression, changes in testes structure and increased malondialdehyde levels and BAX gene expression. TUNEL (Terminal Deoxynucleotidyl Transferase dUTP Nick End Labeling) assay showed an increased number of apoptotic cells. Treatment with lycopene significantly increased testosterone levels, testes weight, and Bcl-2 mRNA expression, improved tubular structure and decreased malondialdehyde levels, BAX mRNA expression and TUNEL-positive cells. The present results show that lycopene exerts beneficial effects in testes, and suggest that supplementation with the tomato-derived carotenoid might be considered a novel nutraceutical strategy for the treatment of varicocele and male infertility.